Native RNA or cDNA Sequencing for Transcriptomic Analysis: A Case Study on Saccharomyces cerevisiae - Wongsurawat, Thidathip; Jenjaroenpun, Piroon; Wanchai, Visanu; Nookaew, Intawat (Frontiers in Bioengineering and Biotechnology, 2022)
Direct sequencing of single molecules through nanopores allows for accurate quantification and full-length characterization of native RNA or complementary DNA (cDNA) without amplification. Both nanopore-based native RNA and cDNA approaches carry out complex transcriptome procedures at a lower cost. However, there are several differences between the two approaches. In this study, we perform matched native RNA sequencing and cDNA sequencing to enable relevant comparisons and evaluation. Using Saccharomyces cerevisiae, a eukaryotic model organism widely used in industrial biotechnology, two different growing conditions are considered for comparison, including the poly-A messenger RNA isolated from yeast cells grown in minimum media under respirofermentative conditions supplemented with glucose (glucose growth conditions) and from cells that had shifted to ethanol as a carbon source (ethanol growth conditions). Library preparation of direct RNA sequencing is shorter than direct cDNA sequencing. The sequence characteristics of the two methods were different; however, differential gene expression analysis derived from the two approaches are comparable. The unique feature of direct RNA sequence is RNA modification, we found that the RNA modification at 5’ end of transcript was underestimated due to the 3’ bias behavior of the direct RNA sequencing. Our comprehensive evaluation from this work could help researchers make informed choices when selecting an appropriate long-read sequencing method for understanding gene functions, pathways, and detailed functional characterization.